Faster and steeper is feasible: Modeling deeper decarbonization in a Northeastern U.S. State. (February 2021) - Roberts, J. Timmons; Veysey, Jason; Traver, Daniel; Gross, Benjamin; Cotler, Brett
Highlights: Using currently available technologies, states can much more rapidly reduce their greenhouse gas emissions than expressed in widely-adopted 80% by 2050 targets. Using shorter-term climate impacts of leaked methane from natural gas and landfills significantly increases estimated state emissions and makes getting to zero more difficult. Rapid decarbonization requires an immediate halt of purchases of new fossil-fuelled equipment, including vehicles, power plants, and heating systems, and decommissioning of natural gas infrastructure. Rapid emissions reductions can be achieved by electrification of transportation and building heat. Estimated costs of reaching 80% carbon reductions by 2040 were not significantly higher than doing so by 2050; 2030 targets are more expensive because they require retiring equipment early. Changing behaviors by households reduced emissions, but these scenarios ended up being largely redundant with technological change; they did meaningfully lower the cost of decarbonization. Modeling the final 20% of emissions reductions was impossible because we lack understanding of state industrial processes and other sources of emissions like landfills and land-use Abstract: Given the lack of federal leadership on climate change in the United States, planning and action at the state and local levels are crucial. However, many state and local plans are built around targets based on outdated climate science such as 80% emissions reductions by 2050. The IPCC 2018 report suggests that wealthy countries must go substantially further in order to reduce the worst effects of anthropogenic climate change. This study involved a team consisting of university researchers and the research institute that originally developed modeling in a consulting role for the state of Rhode Island, to assess the viability of more rapid decarbonization pathways for Northeastern U.S. states. The goal was to provide new insights on possibilities and challenges for major economic sectors like housing, transportation, and industrial emissions. The findings suggest that by adopting existing technologies, 70–80 percent reductions can be reached by 2030, 2040 or 2050. Methane leakage from natural gas transmission and landfills remains a major obstacle to complete decarbonization, as are do industrial emissions and air travel. The work provides first-estimates of sectoral and overall costs of these transitions, compared to maintaining existing infrastructure. A final analysis provides an initial examination of what impact modest behavioral changes would make on the speed and cost of decarbonization at the state level. We describe the context and generalizability of the study, its methods and findings, and suggest directions for future work.